Environmental education and training in industry: Changing orientations and practice? - Heila Lotz (Environmental Association of Southern Africa, 1999)
This paper is a developing story of an emerging pictnre of how environmental education processes are being I can be shaped in industry settings. The paper argues that environmental training in industry can no longer trundle along 'business as usual' pathways, nor can it ignore the changes in education and training policies or environmental management practices. The paper points to current narrow orientations to environmental training, and the tendency in industry to design training programmes which are reactive and follow a 'default' approach to environmental management. It argues for a new look at the significant role that education and training might play in the implementation of preventative environmental management strategies, and notes that new orientations to environmental education and training are more likely to support a re-orientation of environmental management processes. The paper therefore· reflects dimensions of the methodological debates in environmental education and training in industry, debates which, in South Africa, are gradually centering in on two key shaping forces: the integrated and applied competence orientation of the outcomes-based National Qualifications Framework and the international trend towards Preventative Environmental Management. These two orienting concepts are beginning to provide a framework for discussion about environmental education and training methods and processes in industry settings, which the paper aims to open up.